2022
DOI: 10.1055/s-0042-1750138
|View full text |Cite
|
Sign up to set email alerts
|

Combined Use of Negative Oral Contrast and Ranitidine for Magnetic Resonance Cholangiopancreatography: A Randomized Controlled Trial

Abstract: Objective Magnetic resonance cholangiopancreatography (MRCP) is a noninvasive imaging modality to study pancreaticobiliary tree. The primary aim of this study was to compare the image quality of MRCP obtained with the use of ferric ammonium chloride (negative oral contrast) with that of combined use of ferric ammonium chloride and ranitidine (administered orally). Secondary aim was to determine the interobserver agreement between the assessing radiologists. Materials and Methods The study was a singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
0
0
Order By: Relevance
“…Govindarajan et al [ 11 ] concluded that date syrup can be used as a negative oral contrast agent for GI signal suppression during MRCP to improve visualization of various pancreaticobiliary structures. Ferric ammonium chloride (hematinic) and ferric ammonium citrate were also found to be a good MR contrast agent [ 12 , 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Govindarajan et al [ 11 ] concluded that date syrup can be used as a negative oral contrast agent for GI signal suppression during MRCP to improve visualization of various pancreaticobiliary structures. Ferric ammonium chloride (hematinic) and ferric ammonium citrate were also found to be a good MR contrast agent [ 12 , 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%